2019
DOI: 10.3390/su11143879
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sustainable Urban Logistics: Creating Sustainable Urban Freight Transport on the Example of a Limited Accessibility Zone in Gdansk

Abstract: The purpose of the article is to identify the conditions for the implementation of deliveries in the Limited Accessibility Zone (LAZ) in Gdansk, based on interviews conducted among suppliers in October 2018. Another goal is to identify guidelines for the need to create a new transport policy for cities, which will be in line with sustainable urban logistics. The presented analysis is not an economic or technical analysis of an executive nature. It focuses on indicating the nature of the impact of factors condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 3 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…Although there are papers on urban logistics, in Poland [17,18,[24][25][26][27][28][29][30][31][32][33][34][35] this field remains an area where there is still need of research and data to introduce innovative solutions, and above all to broaden awareness that city logistics is no less important than commuters mobility and that these are not separate but mutually dependent areas. There is a need for cooperation between the private and public sector.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are papers on urban logistics, in Poland [17,18,[24][25][26][27][28][29][30][31][32][33][34][35] this field remains an area where there is still need of research and data to introduce innovative solutions, and above all to broaden awareness that city logistics is no less important than commuters mobility and that these are not separate but mutually dependent areas. There is a need for cooperation between the private and public sector.…”
Section: Discussionmentioning
confidence: 99%
“…The researched metropolis authorities are aware of the need for changes in the organization of supplies, which is confirmed by the OMG-G-S Mobility Strategy [20], in which an attempt was made to designate potential locations for urban consolidation centers serving the Tricity area. However, research carried out in the LAZ area in Gdansk in 2013-2016 [17] showed that the resistance of tenants of ground-store commercially used floors is very high, so the authorities are afraid to take action. As regards the organization of deliveries to the LAZ in the city center, consultations concerning this zone were convened at the end of 2017, but they were not very popular.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The environmental impact, in this case being emissions, can be measured using a formula that considers volume, distance and resource consumption of a single truck. Results obtained in this way can be used as guidelines for introducing tolls, dividing urban areas into zones with different principles (e.g., Limited Accessibility Zones) and, thus, reduce road freight transport in cities [27,28]. A great reduction of the carbon footprint and anthropogenic emissions in urban areas may also be obtained by bringing into service more vehicles powered with alternative fuels, especially electrically [29].…”
Section: Literature Overviewmentioning
confidence: 93%
“…Both vehicles are not yet common in Brazil for cargo transportation. However, both can environmentally benefit cargo transportation and can be incorporated into a sustainable urban logistics plan [80].…”
Section: Freight Policies Analysismentioning
confidence: 99%